STRES AKADEMIK SISWA SEKOLAH DASAR DI MASA PANDEMI COVID-19: STUDI PADA BIMBEL CADIAK PANDAI KABUPATEN SOLOK - NUR HASANAH; NURUS SA'ADAH (Universitas Islam Negeri Mataram, 2021)
Abstract: Online learning is a scenario designed by the Ministry of Education and Culture in anticipating the spread of the Covid-19 outbreak and is a challenge for everyone to adapt to the new learning model. The online learning process has an impact on elementary school students in the form of academic stress. Stress has become a regular and unavoidable part of life. Stress can be felt by everyone and in unspecified places, such as at home, school, work, and society. This study uses a qualitative method by conducting a case study. Taking research subjects using the purposive sampling technique. Methods of data collection using interviews, observation and recording. Data analysis was carried out through the stages of data reduction, data visualization, verification and drawing conclusions. Researchers use triangulation to see the validity of the data. The results of the study indicate that the online learning method is not sufficient to provide good habituation to elementary school students, with the large number of assignments given and the short collection deadline can cause stress to students